2015
DOI: 10.7567/apex.8.063006
|View full text |Cite
|
Sign up to set email alerts
|

Electric-field manipulation of coercivity in FePt/Pb(Mg1/3Nb2/3)O3–PbTiO3heterostructures investigated by anomalous Hall effect measurement

Abstract: The effect of electric field (E-field) on the magnetism of FePt thin films in FePt/0.7Pb(Mg1/3Nb2/3)O3–0.3PbTiO3 (PMN–PT) heterostructures was investigated by anomalous Hall effect measurement. For FePt films of different thicknesses, the coercivity vs E-field curves show a typical butterfly-like loop behavior. Further results indicate that the coercivity variation is composed of the volatile symmetrical butterfly-like loop and nonvolatile hysteresis loop-like parts, which originate from the volatile and nonvo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Hence, a moderate magnetocrystalline anisotropy with designed in-plane orientation may serve as the third approach to electric-field control of the nonvolatile 180° magnetization reversal, without additional fabrication costs for the patterned nanomagnet or an induced antiferromagnetic pinning layer . Finally, we would like to mention that although the charge-mediated nonvolatile ME effect has already been confirmed in complex oxides with a low carrier density and ultrathin FM metal, it is negligible for our 20 nm thick Fe film because it is effective only within 1–2 unit cells near the interface. , Nevertheless, charge and strain comediated coexistence of volatile and nonvolatile magnetization is still accepted and under discussion in similar FM/FE structures. A full understanding of the converse ME effects in multiferroic heterostructures is awaited.…”
Section: Resultsmentioning
confidence: 80%
“…Hence, a moderate magnetocrystalline anisotropy with designed in-plane orientation may serve as the third approach to electric-field control of the nonvolatile 180° magnetization reversal, without additional fabrication costs for the patterned nanomagnet or an induced antiferromagnetic pinning layer . Finally, we would like to mention that although the charge-mediated nonvolatile ME effect has already been confirmed in complex oxides with a low carrier density and ultrathin FM metal, it is negligible for our 20 nm thick Fe film because it is effective only within 1–2 unit cells near the interface. , Nevertheless, charge and strain comediated coexistence of volatile and nonvolatile magnetization is still accepted and under discussion in similar FM/FE structures. A full understanding of the converse ME effects in multiferroic heterostructures is awaited.…”
Section: Resultsmentioning
confidence: 80%
“…24−26 As for the FM component, we choose the binary alloy, FePt, due to its large magnetic anisotropy and magnetostriction constant. 27,28 We demonstrate that multiple M r states can be reversibly written as storage data bits in a FePt/PMN-PT heterostructure by electric field. These magnetic signals are nonvolatile and steady enough to retain written information.…”
Section: Introductionmentioning
confidence: 94%
“…In this article, a (011)-oriented 0.7Pb­(Mg 1/3 Nb 2/3 )­O 3 -0.3PbTiO 3 (PMN-PT) single crystal is selected as a FE substrate for its electric field controlling reversible and nonvolatile strain with the application of electric field. As for the FM component, we choose the binary alloy, FePt, due to its large magnetic anisotropy and magnetostriction constant. , We demonstrate that multiple M r states can be reversibly written as storage data bits in a FePt/PMN-PT heterostructure by electric field. These magnetic signals are nonvolatile and steady enough to retain written information.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, one experimental work [23] showed that the value of coercivities increased with the increase of the recoverable compressive misfit strain in the L1 0 FePt (3 nm) thin film deposited on PMN-PT substrate. The reason is that when the PMN-PT substrate is polarized under an applied electric field, a recoverable strain is induced by a converse piezoelectric effect, which can pass on to the L1 0 FePt thin film and thus manipulate the magnetic anisotropy of the film through the converse magnetostriction effect.…”
Section: Introductionmentioning
confidence: 99%